Secrets of F.P.1 Based on a Novel by Curt Siodmak - Siodmak, Curt (Deutsche Filmklassiker, 2021)
An impressively staged melodrama, with a decidedly original theme, is the present tenant of the Seventh Avenue Roxy's screen. It is an English language edition of a German production and, like its counterpart, is labeled "F.P. 1", a title which is presumed to mean "Floating Platform No. 1". It is much like a modern Jules Verne story, for the main idea is that of having a landing platform for airplanes anchored in mid-Atlantic. [www.nytimes.com]